Contemporary Political Theory - Colin Farrelly (SAGE Publications, 2004)
This text provides an up to date account of how things currently stand in political philosophy, and will provide an excellent introduction for students from any background. It gives a lucid and careful account of the central controversies and sites of disagreement in political theory over the last thirty years and rather than sacrifice theoretical sophistication and nuance for the sake of clarity and accessibility, it admirably achieves both